1997
DOI: 10.1007/pl00012279
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Bacillus Calmette Guérin Lymphadenitis

Abstract: Although its protective effect is contested and the risk of contracting tuberculosis is rather low nowadays, BCG vaccination is frequently performed. Changes of strain repeatedly led to an increased complication rate. In Austria between 1990 and 1991, of 3386 newborn babies (Strain Pasteur) 116 developed lymphadenitis 3 to 28 weeks after vaccination. The affected children received four types of treatment: nothing specific, isoniazid, or surgery with and without isoniazid. Surgical treatment was found to be nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 13 publications
1
38
0
1
Order By: Relevance
“…However, some complications may occur in immune competent children. Disseminated BCG infection in children usually manifests in the first year of life, but an adult case of reactivation of BCG in an AIDS patient more than 30 years after vaccination has also been reported [2].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, some complications may occur in immune competent children. Disseminated BCG infection in children usually manifests in the first year of life, but an adult case of reactivation of BCG in an AIDS patient more than 30 years after vaccination has also been reported [2].…”
Section: Introductionmentioning
confidence: 97%
“…Common BCG vaccination-related complications are lymphadenitis and abscess limited to the region of inoculation [2]. There were cases of chest wall abscess as a complication of BCG vaccination in infants [3,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hengster et al found that culture yield percentage decreased with time, with 46% of cases having positive cultures in the first 20 weeks of receiving the BCG vaccination compared to 0% after 20 weeks. 22 The use of GeneXpert, a rapid and automated nucleic acid amplification test, confirmed the presence of M. tuberculosis, BCG strain, in the present case.…”
Section: 2mentioning
confidence: 55%
“…A todos se les efectuó drenaje, extirpación y biopsia de los nódulos axilares, incluso en forma repetida, ya que se ha descrito que la propensión a desarrollar resistencia posterior apoya la resección quirúrgica precoz y la escisión de nódulos axilares persistentes para eliminar un foco crónico de infección 41 . Todos tuvieron una respuesta clínica lenta, pero satisfactoria y a la fecha se encuentran clínicamente sin enfermedad BCG, aunque el caso 4 presenta un cuadro dermatológico de etiología poco clara, sin elementos histológicos de vasculitis leucocitoclástica cutánea, enfermedad que ha sido asociada a Salmonella Enteritidis, reportada previamente en pacientes con deficiencia del receptor b-1 de IL-12 [42][43][44] . Otras alternativas terapéuticas como el uso de interferón γ [45][46][47] no fueron consideradas, dada la evolución favorable con los esquemas de tratamiento usados.…”
unclassified